2020
DOI: 10.1002/jmv.26272
|View full text |Cite
|
Sign up to set email alerts
|

An open call for influenza vaccination pending the new wave of COVID‐19

Abstract: We have read the study of Yue et al 1 with great interest. They reported influenza coinfection among 307 coronavirus disease 2019 (COVID-19) patients as 57.3%. The study included a period

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…In previous studies, the frequency and clinical outcomes of co‐infection with influenza virus were variable 16,17 . Co‐infection was uncommon in Northern California, United States (0.9%), 18 and Turkey (0.54%) 19 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, the frequency and clinical outcomes of co‐infection with influenza virus were variable 16,17 . Co‐infection was uncommon in Northern California, United States (0.9%), 18 and Turkey (0.54%) 19 .…”
Section: Discussionmentioning
confidence: 97%
“…CT, computed tomography; IFV, influenza A virus; IgM, immunoglobulin M; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2The CT features, including the location, extent and distribution of each abnormality are presented in Table3. The median time from onset of symptoms to CT scan were 18 (12-23) days for patients with SARS-CoV-2 infection only and 20(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) days for patients with co-infection (p = .487). Four patients (two with SARS-CoV-2 infection only and two with co-infection) had normal CT scan.…”
mentioning
confidence: 99%
“…To date, this disease has spread in many countries and has resulted in millions of cases of infection and thousands of deaths all over the world. 7 Recently published reports of concurrent infections of other respiratory viruses such as influenza virus [8][9][10][11][12] and human metapneumovirus 13,14 with SARS-CoV-2 infection have suggested that coinfection could affect the morbidity and mortality ratio. In addition to these, due to the wide range of symptoms in patients and relatively higher mortality in comparison with the global rate, 15 in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…As the bulk of the second wave of COVID-19 approaches, there is the additional worry of influenza season. Although there is evidence demonstrating that measures used to control the spread of COVID-19 decreases influenza activity substantially, there are still reports of co-infection [ 17 19 ]. This co-infection has the potential to complicate prognosis and is especially concerning in high-risk groups such as older individuals, those with chronic diseases and the immunocompromised [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%